Sensitization Profile to Allergens in Patients Using Multi-Test II - Maniglia,Sergio Fabricio (2014)
Introduction Medical intervention in allergies has broadened its perspective, also focusing in the quality of life of patients. Patients are instructed, before using pharmacotherapy agents, to avoid the causal agent. Objective This study aims to analyze the sensitization profile of patients with allergic complaints and identify possible characteristics specific to each age group and gender. Methods A descriptive cross-sectional study included data collected from medical records (from Multi-Test II database, Lincoln Diagnostics Inc. Decatur, Illinois) of 1,912 patients who underwent skin prick test from March to October 2013. Patients were organized and analyzed according to gender, age, and results of the allergens subtypes tested. Results The study was composed of 1,912 patients (60% male and 40% female) of ages between 3 and 87 years. Positive tests were more prevalent in quantity and intensity with the mites Dermatophagoides pteronyssinus and Dermatophagoides farinae, each with 60% of the total analyzed. In second place were pollens, especially Dactylis glomerata and Festuca pratensis. Conclusion The female and male sexes were equally atopic. Fungi and epithelia of dog and cat were not considered potential aeroallergens that could cause symptoms. However, mites are common in Paraná, Brazil. Further studies regarding the pollens are needed, as this study result diverged from the literature.